Scooby-Doo! World of Mystery 34 Iran - Persepolis - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
The gang visit the spooky ruins of Persepolis in Iran and Shaggy and Scooby get into a spot of bother!
Keywords: Juvenile literature-Fiction